Effects of Niacin on Resistance to Enterotoxigenic Escherichia coli Infection in Weaned Piglets - Zhen, Rui; Feng, Junsen; He, Dongsheng; Chen, Yibo; Chen, Tianbao; Cai, Weiyou; Xiong, Yunxia; Qiu, Yueqin; Jiang, Zongyong; Wang, Li; Yi, Hongbo (Frontiers in Nutrition, 2022)
NNicotinic acid (NA) has been used to treat different inflammatory disease with positive influence, the mechanisms by which NA exerts its anti-inflammatory effects remain largely undefined. Here we proposed a new hypothesis that NA manipulated endogenous antimicrobial peptides (AMPs) which contributed to the elimination of enterotoxigenic Escherichia coli (ETEC) K88, and thus affects the alleviation of inflammation. Therefore, an experiment in weaned piglets treated with 40 mg NA for 3 days before ETEC K88 challenge was designed to investigate the effects of NA on resistance to enterotoxigenic Escherichia coli infection in weaned piglets.The results showed that NA alleviated the clinical symptoms of weaned piglets infected with ETEC K88. NA significantly reduced the amount of ETEC K88 in the spleen and liver (P < 0.05). The intestinal morphological damage caused by ETEC K88 infection was alleviated by NA in weaned piglets. In addition, NA significantly alleviated the expression of inflammatory cytokine (Interleukin-6 (IL-6), Interleukin-8 (IL-8), tumor necrosis factor-α (TNF-α)) in the serum and intestines of weaned piglets infected with ETEC K88 (P < 0.05). NA significantly increased the content of secretory IgA (SIgA) and the expression of antimicrobial peptides (porcine β defensin-2 (pBD2), protegrin1-5 (PG1-5) and PR39) in intestines of weaned pigs. NA increased the diversity of microflora in colonic contents, while NA significantly reduced the relative abundance of Bacteroidetes, Bacteroidales and bacteroidia in weaned piglets infected with ETEC K88 (P < 0.05). Furthermore, the NA group significantly reduced the level of HDAC7 in jejunum (P < 0.05) and increased the level of SIRT1 in the colon compared with the Control group. Moreover, NA significantly increased the levels phosphorylation of histone H3 at Ser10 (pH3S10) in ileum and the levels of acetylation of lysine 9 on histone 3 (acH3K9) and acH3K27 in colon (P < 0.05) in weaned piglets infected with ETEC K88 (P < 0.05). In conclusion, NA can alleviate the clinical symptoms, the damage of intestinal morphology, and intestinal inflammation in weaned piglets infected ETEC K88 through enhancing the expression of endogenous AMPs by associating the histone acetylation modification.